ANALISA KINERJA MESIN REFRIGERASI RUMAH TANGGA DENGAN VARIASI REFRIGERAN - Amrullah, Amrullah; Djafar, Zuryati; Piarah, Wahyu Haryadi (P3M Politeknik Negeri Indramayu, 2017)
The most important component in the refrigerator is the refrigerant. The refrigerant absorbs heat from one side and throw it to another side through the mechanism of evaporation and condensation. This research aims to develop a refrigeration machine using different refrigerants that can be observed with the performance of the compressor, evaporator performance and COP, and hoped this research can show the installation as a medium of learning in applying the working principle of refrigerator. The research method was experimental at setting 8 refrigeration machine with data collection for the pressure and temperature of R-12 and R-134a were measured at the compressor inlet and outlet for 300 minutes. Determining the value of the enthalpy at any point by using REFPROP program. The use of different refrigerants in a refrigeration machine indicates that the refrigerant R-134a better than R-12. It can be seen after 300 minutes for R-134a, compressor performance 29.4 kJ / kg, the performance of the evaporator is 144.5 kJ / kg, COP 4.9 while for R-12 compressor performance 21.8 kJ / kg, the performance of the evaporator is 12.3 kJ / kg, COP 4.6.